Analysis of factors affecting fatigue in emergency medicine residents: A nationwide, cross-sectional, descriptive study - Ali Batur (Turkish Journal of Emergency Medicine)
OBJECTIVES: Emergency physicians may experience intense fatigue and burnout due to factors related to occupational conditions. The group experiencing burnout most frequently among physicians is emergency medicine (EM) physicians, with 63%. They also endure high levels of fatigue. This study evaluated the fatigue levels and factors of fatigue in EM residents nationwide. It aimed to determine the factors affecting fatigue. METHODS: The study includes EM residents working across the country between January 2024 and April 2024. It was conducted using a survey. The survey included the Maslach Burnout Inventory (MBI), the Chalder Fatigue Scale, and questions about demographic characteristics. Multivariate logistic regression analysis was used to analyze the data. RESULTS: The median age of participants was 28 years (interquartile range = 3), and 203 (56.4%) were male. Factors affecting the level of fatigue were analyzed by multivariate logistic regression analysis. The gender (male) (odds ratio [OR] =0.322, 95% confidence interval [CI] =0.128–0.812) and the daily sleep duration (OR = 0.589, 95% CI = 0.423–0.822) variables had a negative effect on fatigue. Depression in medical history increased the likelihood of fatigue (OR = 3.515, 95% CI = 0.930–13.287). Emotional exhaustion (EE) (OR = 1.082, 95% CI = 1.037–1.130) and depersonalization (OR = 1.097, 95% CI = 1.015–1.186) increased the fatigue level. However, personal accomplishment had no significant effect on fatigue (OR = 1.019, 95% CI = 0.966–1.075). CONCLUSIONS: Being female gender, having shorter daily sleep duration, having a diagnosis of depression in medical history, and having higher levels of depersonalization and EE from MBI subdimensions increase the level of fatigue. Optimizing the sleep duration of EM residents and supporting their psychological health will prevent fatigue and fatigue-related problems.